Analysis of Teacher Training in Educational Robotics with URA Workshops - Lago, Maria Eduarda; de Lyra Junior, Isaac; Queiroz, Brenda; da Silva, Melquiades; Pereira, Johnatan; Burlamaqui, Aquiles; Santana Jr, Orivaldo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This article aims to present and analyse a model for a Educational Robotics teacher training course for public brazilian schools teachers. The use of technologies in the classroom has become common in many schools over the world and robotics is an example of these technologies, changing this educational environment that for long remained still. However, the Education professionals don’t have the appropriate skills due the fact that such technologies aren’t presented during their academic education. Due to this shortfall in such technologies and a great interest shown from education professionals, the project URA (One Robot per Student) decided to promote a course of Educational Technologies and Methodologies, focusing on active learning methodologies for a better understanding of mechanics, electronics and programming and development of these skills. During the whole process, the enrolled professors had access to research labs, as well as high skilled tutors and professors in the tech area. At the end of the course, all the enrolled were able to develop, by themselves, robotics projects for educational purposes.